Long-term cytotoxic effects of contemporary root canal sealers - Emmanuel Joao Nogueira Leal da SILVA; Carolina Carvalho SANTOS; Alexandre Augusto ZAIA (Journal of Applied Oral Science, 2013)
Objectives The aim of the present study was to investigate the effects of root canal sealers on the cytotoxicity of 3T3 fibroblasts during a period of 5 weeks. Material and Methods Fibroblasts (3T3, 1×105 cells per well) were incubated with elutes of fresh specimens from eight root canal sealers (AH Plus, Epiphany, Endomethasone N, EndoREZ, MTA Fillapex, Pulp Canal Sealer EWT, RoekoSeal and Sealapex) and with elutes of the same specimens for 5 succeeding weeks after immersing in simulated body fluid. The cytotoxicity of all root canal sealers was determined using the MTT assay. Data were analyzed using ANOVA and Tukey's test. Results RoekoSeal was the only sealer that did not show any cytotoxic effects (p<0.05). All the other tested sealers exhibited severe toxicity initially (week 0). MTA Fillapex remained moderately cytotoxic after the end of experimental period. Toxicity of the other tested sealers decreased gradually over time. The evaluated root canal sealers presented varying degrees of cytotoxicity, mainly in fresh mode. Conclusions RoekoSeal had no cytotoxic effect both freshly mixed and in the other tested time points. MTA Fillapex was associated with significantly less cell viability when compared to the other tested root canal sealers.